Association of DHEAS levels with COVID19 severity, gender, age, comorbidities, and management strategies - Tahereh Jamali; Sussan Kaboudanian Ardestani; Mohammad-Reza Vaez-Mahdavi; Arezou Rezaei; Mohammad Mehdi Naghizadeh; Fatemeh Tuserkani; HosseinAli Khazaei; Ali Khodadadi; Bahman Khazaei; Keivan Latifi; Tooba Ghazanfari (Scientific Reports)
Abstract COVID-19 has globally impacted millions. This study investigates DHEAS (dehydroepiandrosterone sulfate) as a factor for COVID-19 progression, analyzing its relationship with disease status, temporal patterns, age, gender, and comorbidities to improve outcomes. DHEAS was quantified with a competitive chemiluminescent immunoassay. We conducted DHEAS analysis across different days. COVID-19 patients, particularly inpatients, have lower DHEAS levels compared to controls. DHEAS levels in COVID-19 patients showed a dynamic pattern, with an initial decline followed by recovery. The scatter plot analysis suggested COVID-19 could increase the age-related decline in DHEAS among males. Comorbidities, including hypertension, heart disease, and diabetes mellitus, were prevalent among COVID-19 patients and correlated with disease severity. Hypertension moderated the relationship between hospitalization and DHEAS, especially in females. Our findings showed a significant association between lower DHEAS and COVID-19 severity, along with temporal dynamics. COVID-19’s potential to increase the age-related decline in DHEAS, especially in males, underscores its intricate relationship with age. Hypertension’s influence on DHEAS suggests a gender-specific effect, emphasizing tailored management approaches. These findings offer valuable insights into the interaction between COVID-19, hormonal dynamics, and demographic factors, suggesting that DHEAS levels may play a role in the pathophysiology of the disease and could be considered alongside other markers.